PRAK Is Required for the Formation of Neutrophil Extracellular Traps - Wang, Yan; Wang, Yuqing; Wu, Jia; Liu, Chen; Zhou, Yu; Mi, Ligu; Zhang, Yu; Wang, Wei (Frontiers in Immunology, 2019)
Neutrophil extracellular traps (NETs) are one of the most powerful and specific tools for neutrophils to clean up extracellular microbes, but the mechanisms of NETosis under infection are scarcely studied. In this study, by examining the neutrophils from human peripheral blood and mouse abdomen, we demonstrated that PRAK dysfunction resulted in a significantly reduced NET formation and elevated apoptotic cells. Furthermore, PRAK dysfunction could lead to impaired NET-mediated antibacterial activity and shorten the survival of mice with CLP-induced sepsis. Mechanism studies revealed that attenuated NET formation in PRAK dysfunctional neutrophils correlated with unregulated reactive oxygen species (ROS), which triggered apoptosis through excessive autophagy. The imbalance of NET formation and apoptosis was further regulated by treatment with lower ROS in hypoxia. Here, we propose a novel candidate, PRAK, which can sense the oxidative stress and regulate the releasing of ROS, may be the master molecular switch to regulate the NETosis-apoptosis axis of neutrophils.